Nivel De Estrés Académico Y Estrategias De Afrontamiento En Los Estudiantes Universitarios (2023)
The main objective of this study was to analyze the level of academic stress and coping strategies in university students. The method in which it is framed is quantitative, with a methodology of correlational scope and non-experimental design. A sample of 30 university students in the seventh, eighth, ninth and tenth semesters of psychology at the Universidad Antonio Nariño at the Riohacha headquarters, was obtained. The instruments applied were: SISCO Academic Stress Inventory to evaluate the psychological, behavioral, and physical impact of stress and the Modified Coping Strategies Scale (EEC - M) to evaluate coping strategies